2000
DOI: 10.1007/s004240000127
|View full text |Cite
|
Sign up to set email alerts
|

Ca-sensitive and Ca2+-insensitive exocytosis in maize coleoptile protoplasts

Abstract: Ca2+ and osmotic driven extension of the surface area of maize coleoptile protoplasts was investigated using capacitance measurements and photolysis of the caged compound DM-nitrophen. Protoplasts responded to an elevation of cytoplasmic Ca2+ (Ca(i)) with a rapid burst in capacitance reaching a maximal increase of 1.3+/-1.1% over the resting cell capacitance. Subsequent lowering of the osmotic potential in the external medium by 210 mosmol caused a further increase in Cm by 26+/-6%. These data indicate two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Similar calcium-independent, tension-regulated lipid insertion is found in plant cells (53) and osmotically swollen neurons (37,54). Morris and colleagues argue from cellular energy economy that a tension-regulated lipid insertion mechanism is not only experimentally evident but also theoretically appealing (35).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar calcium-independent, tension-regulated lipid insertion is found in plant cells (53) and osmotically swollen neurons (37,54). Morris and colleagues argue from cellular energy economy that a tension-regulated lipid insertion mechanism is not only experimentally evident but also theoretically appealing (35).…”
Section: Discussionmentioning
confidence: 77%
“…Less clear is how these stretch-induced responses, good or bad, are affected by the rates at which epithelial cells are stretched and the consequent fluctuations in membrane tension. Some studies addressed cell injury and plasma membrane rupture when cells are stretched a very high strain rates, and how they recover afterward (53,62). It has also previously been reported that cells stretched at 60 cycles/min sustain greater injury than cells stretched more slowly at 15 cycles/min (63).…”
Section: Discussionmentioning
confidence: 99%
“…The high turgor pressure in plants might force the host membrane towards the viral membrane, leading to fusion. This hypothesis is plausible because it is well known that physical pressure and membrane tension can catalyze membrane fusion (Shillcock and Lipowsky 2008; Thiel et al 2000). …”
Section: Transfer Of Dna From the Virus Particle Into The Host Cellmentioning
confidence: 99%
“…Secretion activity independent of [Ca# + ] i has been intimated from work with barley aleurone protoplasts (Homann & Tester, 1997) and more recently in studies of guard cell protoplasts (Homann, 1998) and maize coleoptile protoplasts (Thiel et al, 1999). Homann & Tester (1997) found a small, but steady rise in capacitance that was independent of [Ca# + ] i level in the patch pipette.…”
Section: Coupling Secretion To Cytosolic-free Ca# + Concentrationmentioning
confidence: 99%